Computed Tomography Analysis of the Feline Infraorbital Foramen and Canal - Davis, Lily V.; Hoyer, Naomi K.; Boscan, Pedro; Rao, Sangeeta; Rawlinson, Jennifer E. (Frontiers in Veterinary Science, 2021)
Feline skull anatomic variation is plain to see with casual observation. Obtaining an in-depth under-standing of this anatomic variety is critical to performing safe and effective regional anesthesia for dental procedures. Maxillofacial anatomic variability is proven to impact the placement and efficacy of nerve blocks in dogs and horses, but similar studies have not been performed in cats. This study’s main objective was to evaluate the anatomy of the infraorbital foramen and canal in relation to regional an-atomic landmarks in brachycephalic and mesaticephalic cats. Significant anatomic variability particularly in brachycephalic skulls was identified.